Dasar Tujuan Pendidikan Hati menurut Ibnu Qayyim Al-Jauziyyah - Arafah, Tiara Pelangi; Nur Fuad, Ai Fatimah (Attractive : Innovative Education Journal, 2024)
This research examines the foundations and goals of heart education according to the views of Ibnu Qayyim Al-Jauziyah, an Islamic thinker who lived in the 14th century AD. Heart training is considered a central aspect in the development of individual and social character, and Ibn Qayyim is considered one of the figures who made an important contribution to this. The research method is literary analysis of Ibnu Qayyim Al-Jauziyah's work which focuses on education of the heart. The research results show that his thinking is based on moral values, ethics and Islamic principles which are the basis for education of the heart. Furthermore, according to Ibnu Qayyim Al-Jauziyah, the core educational goals are related to noble morals, spiritual awareness and self-control. Keywords: Basic Objective, Heart education, Ibnu Qayyim Al-Jauziyyah